miR-222 inhibits pathological cardiac hypertrophy and heart failure - Liu, Xiaojun; Li, Haobo; Hastings, Margaret H; Xiao, Chunyang; Damilano, Federico; Platt, Colin; Lerchenmüller, Carolin; Zhu, Han; Wei, Xin Paul; Yeri, Ashish; Most, Patrick; Rosenzweig, Anthony (Cardiovascular research, 2024)
Physiological cardiac hypertrophy occurs in response to exercise and can protect against pathological stress. In contrast, pathological hypertrophy occurs in disease and often precedes heart failure. The cardiac pathways activated in physiological and pathological hypertrophy are largely distinct. Our prior work demonstrated that miR-222 increases in exercised hearts and is required for exercise-induced cardiac hypertrophy and cardiomyogenesis. Here, we sought to define the role of miR-222 in pathological hypertrophy.We found that miR-222 also increased in pathological hypertrophy induced by pressure overload. To assess its functional significance in this setting, we generated a miR-222 gain-of-function model through cardiac-specific constitutive transgenic miR-222 expression (TgC-miR-222) and used locked nucleic acid anti-miR specific for miR-222 to inhibit its effects. Both gain- and loss-of-function models manifested normal cardiac structure and function at baseline. However, after transverse aortic constriction (TAC), miR-222 inhibition accelerated the development of pathological hypertrophy, cardiac dysfunction, and heart failure. Conversely, miR-222-overexpressing mice had less pathological hypertrophy after TAC, as well as better cardiac function and survival. We identified p53-up-regulated modulator of apoptosis, a pro-apoptotic Bcl-2 family member, and the transcription factors, Hmbox1 and nuclear factor of activated T-cells 3, as direct miR-222 targets contributing to its roles in this context.While miR-222 is necessary for physiological cardiac growth, it inhibits cardiac growth in response to pressure overload and reduces adverse remodelling and cardiac dysfunction. These findings support the model that physiological and pathological hypertrophy are fundamentally different. Further, they suggest that miR-222 may hold promise as a therapeutic target in pathological cardiac hypertrophy and heart failure.